Application of Topical Preparations with Combined Effect in the Treatment of Inflammatory Diseases of the Oral Cavity and Pharynx - I.V. Balychevtseva (Zaslavsky O.Yu., 2015)
Acute infectious and inflammatory diseases of the oral cavity and pharynx are common in children and adults. The paper presents the possibilities of managing inflammatory process and pain syndrome, which develop in these diseases, via topical application of modern preparation Tantum Verde®.